Doping Quantum Spin Liquids on the Kagome Lattice. Issue 3 (28th January 2021) - Peng, Cheng; Jiang, Yi‐Fan; Sheng, Dong‐Ning; Jiang, Hong‐Chen
Abstract: The authors review recent density‐matrix renormalization group studies of lightly doped quantum spin liquids (QSLs) on the kagome lattice. While a number of distinct conducting phases, including high temperature superconductivity, have been theoretically anticipated, a tendency toward fractionalized insulating charge‐density‐wave (CDW) states is instead found. In agreement with earlier work [Jiang, Devereaux, and Kivelson, Phys. Rev. Lett . 2017, 119, 067002], results for the t ‐ J model reveal that, starting from a fully gapped QSL, light doping leads to CDW long‐range order with a pattern that depends on lattice geometry and doping concentration such that there is one doped‐hole per CDW unit cell, while the spin–spin correlations remain short‐ranged. Alternatively, this state can be viewed as a stripe crystal or Wigner crystal of spinless holons, rather than of doped holes. From here, by studying generalized versions of the t ‐ J model, these results are extended to light doping of other types of QSLs, including critical and chiral QSLs. These results suggest that doping these QSLs also leads to insulating states with long‐range CDW order. While the superconducting correlations are short‐ranged, they can be significantly enhanced by second‐neighbor electron hopping. The relevance of these numerical results to Kagome materials is also discussed. Abstract : The physics of doped distinct Kagome lattice quantum spin liquids is reviewed and investigated. Density‐matrix renormalization group results reveal that light doping these spin liquids leads to an exotic insulating crystal state of spinless holons rather than of doped holes, which has long‐range charge‐density‐wave order with one doped‐hole per unit cell whose pattern depends on lattice geometry and doping concentrations.